2003
DOI: 10.1002/mrm.10654
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantification of choline compounds in the breast with 1H MR spectroscopy

Abstract: This work describes a methodology for quantifying levels of total choline-containing compounds (tCho) in the breast using in vivo 1 H MR spectroscopy (MRS) at high field (4 Tesla). Water is used as an internal reference compound to account for the partial volume of adipose tissue. Peak amplitudes are estimated by fitting one peak at a time over a narrow frequency band to allow measurement of small metabolite resonances in spectra with large lipid peaks. This quantitative method significantly improves previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
263
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(282 citation statements)
references
References 21 publications
17
263
1
Order By: Relevance
“…Diffusion-weighted MRI can be used to detect changes in the apparent diffusion coefficient (ADC) for tissue water associated with changes in tissue and intracellular structure (Zhao et al, 1996;Gallons et al, 1999;Ross et al, 2003;Moffat et al, 2005). Proton magnetic resonance spectroscopy (MRS) can be used to characterise breast lesions through differences in the ratio of fat and water signals (Chu et al, 1987;Sijens et al, 1988) or the intensity of signal from choline-containing compounds (Bradamante et al, 1988;Katz-Brull et al, 2002;Bolan et al, 2003;Jacobs et al, 2004;Jacobs et al, 2005). Both fat : water ratios (Jagannathan et al, 1998) and choline levels (Preul et al, 2000;Jagannathan et al, 2001;Schwarz et al, 2002;Meisamy et al, 2004) have also been used to monitor treatment-induced changes, and phosphorous MRS has been used to predict response using differences in the levels of phosphocholine or phosphomonoesters (Shukla-Dave et al, 2002a, b;Arias-Mendoza et al, 2004).…”
mentioning
confidence: 99%
“…Diffusion-weighted MRI can be used to detect changes in the apparent diffusion coefficient (ADC) for tissue water associated with changes in tissue and intracellular structure (Zhao et al, 1996;Gallons et al, 1999;Ross et al, 2003;Moffat et al, 2005). Proton magnetic resonance spectroscopy (MRS) can be used to characterise breast lesions through differences in the ratio of fat and water signals (Chu et al, 1987;Sijens et al, 1988) or the intensity of signal from choline-containing compounds (Bradamante et al, 1988;Katz-Brull et al, 2002;Bolan et al, 2003;Jacobs et al, 2004;Jacobs et al, 2005). Both fat : water ratios (Jagannathan et al, 1998) and choline levels (Preul et al, 2000;Jagannathan et al, 2001;Schwarz et al, 2002;Meisamy et al, 2004) have also been used to monitor treatment-induced changes, and phosphorous MRS has been used to predict response using differences in the levels of phosphocholine or phosphomonoesters (Shukla-Dave et al, 2002a, b;Arias-Mendoza et al, 2004).…”
mentioning
confidence: 99%
“…Raw data acquired was then transferred to a PC and processed by advanced signal processing software. The choline-containing compounds concentration was calculated using water as an internal reference [9,10].…”
Section: Mr Imaging Protocolmentioning
confidence: 99%
“…Initially, a simple dichotomous approach based on the presence or absence of the choline peak was shown in some reports (5,6). Furthermore, choline quantification has been proposed using either an internal or an external reference (9,10). Recently, Sardanelli et al (7) showed that breast MRS using the integral value of the choline peak allowed a high level of diagnostic performance, with 84% sensitivity and 89% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the breast, MRS has been shown to be useful for the differentiation between benign and malignant lesions and for the monitoring of early response to neoadjuvant chemotherapy (7)(8)(9). Its diagnostic value for breast cancer is typically based on the detection of elevated levels of choline compounds, which are markers of active tumors (10,11).…”
mentioning
confidence: 99%